PEMBERDAYAAN KADER POSYANDU DALAM PEMBUATAN JELLY BUAH SENDUDUK UNTUK PENCEGAHAN KARIES GIGI BALITA - Telisa, Imelda; Marlindayanti, Marlindayanti; Listrianah, Listrianah (Poltekkes Kemenkes Mataram, 2024)
Toddlers often nibble on items like candy, wafers, cakes, and biscuits. These foods include sucrose, which lowers salivary buffer capacity and increases the risk of tooth decay. Dental caries affects children's nutritional status, prolongs health issues, and interferes with their growth and development by causing pain, making it difficult for them to chew food, and making them cranky. The first way parents can learn about their child's development and progress is through integrated service post. Senduduk fruit, which is abundant in Pipa Putih Village, is rich in flavonoids, saponins, tannins, glycosides, and steroids/triterpenoids. Fruit extract from Senduduk is capable of preventing bacteria from colonizing and plaque from growing on teeth. The purpose of community service is to enable early childhood education teacher cadres and instructors to prepare Senduduk jelly, which helps shield kids' teeth from cavities. Activities included creating a location survey, simulating the creation of Senduduk jelly candy and presenting it to early childhood education cadres and teachers, distributing prepared goods and Senduduk jelly candy recipe pamphlets. The exercise concluded with an assessment of the cadres' performance in a simulated scenario including the preparation of Senduduk jelly for moms attending the Integrated service post. Based on the evaluation results, the understanding of early childhood education cadres and teachers regarding making sedunia jelly can be done well. The average knowledge results of early childhood education cadres and teachers increased from 62 to 78.